Determining Position of the Evaporator in a Smart Classroom Concept Using CFD Method - Permatasari, Rosyida; Ridhoarto, Muhammad Alwan; Cahyati, Sally; Susetyarto, Martinus Bambang (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2021)
Various, different evaporator placements in a room have produced different airflow patterns, temperature distribution, and airflow velocities. In this study, the average room temperature and airflow velocity measured at 27 points of the CFD simulation for 4 positions of the planned evaporator placements were compared to determine the most ideal position based on the comfortable temperature and the maximum airflow velocity pursuant to the SNI 03-6572-2001 recommendation. On Position 1, two evaporators were given to the west wall. Position 2, two evaporators were placed on the south wall. On Position 3, two evaporators were given to the north wall. Moreover, on Position 4, two evaporators were placed opposite to each other where an evaporator was placed on the south wall, and the other evaporator was placed on the north wall. An ANSYS Fluent software was employed to make the CFD simulation. Based on the results of the study, it was found out that Position 2 was the most ideal evaporator placement position since it met the comfortable temperature limit and has the highest number of airflow velocity points meeting the recommended maximum airflow velocity pursuant to the SNI 03-6572-2001 recommendation.